Are we underinvesting in education? - Pierre J Hoffmeyer (EFORT Open Reviews, 2023)
Surgical education used to be simple. ‘See one, do one, teach one’ was Halsted’s (1852–1922) philosophy and for the better parts of the 19th and 20th centuries that was to be the way forward (1). Back in the day, students of surgery would actually pay the master for the educational expertise he dispensed. Surgery was generally a low-tech affair using instrumentation straight out of the forge or the workshop with no accreditations or bureaucratic approval processes needed. Surgical intervention was such that a so-inclined individual could learn by observation and then train, in the best of cases under the eye of a mentor, and then rapidly become a solo operator. The gamut of possible procedures could be mastered by a single surgeon, the dream of present-day administrators, although even then, some were more skilled at amputation and others at hernia repair. Economically all of this made sound sense and with this type of educational system hospitals did not have much to invest in the education of future surgeons.